Strange Days: Adult Physical Activity and Mental Health in the First Two Months of the COVID-19 Pandemic - Madelaine Gierc; Negin A. Riazi; Matthew James Fagan; Katie M. Di Sebastiano; Mahabhir Kandola; Carly S. Priebe; Katie A. Weatherson; Kelly B. Wunderlich; Guy Faulkner (Frontiers Media S.A., 2021)
Background: In addition to its physical health benefits, physical activity is increasingly recognized as a means to support mental health. Regular moderate-to-vigorous physical activity (MVPA) is associated with improved mental well-being, reduced likelihood of developing mental illness, and improved symptom management. Despite these benefits, most people fail to achieve minimum recommended levels of MVPA. Population levels of physical activity have further declined since the onset of the COVID-19 pandemic and implementation of public health measures (e.g., shelter-in-place protocols). The potential impact of this decline on mental heath outcomes warrants ongoing investigation.Purpose: To investigate associations between changes in MVPA and mental health (depressive symptoms, anxiety symptoms, and life satisfaction) in adults impacted by the COVID-19 pandemic.Method: Research followed a cross-sectional design. English-speaking adults were invited to complete an online questionnaire. MVPA was assessed retrospectively (before COVID-19) and currently (during COVID-19) with the International Physical Activity Questionnaire. Mental health was assessed with the Patient Health Questionnaire, 9-Item (PHQ-9), the Generalized Anxiety Disorder, 7-Item (GAD-7), and the Satisfaction with Life Scale (SWLS). Regression was used to assess relationships between MVPA and mental health. ANOVA with follow-up tests examined whether participants who differed in mental health status (e.g., no symptoms vs. severe symptoms) differed in their change in MVPA. T-tests were used to examine differences in mental health symptomatology between participants who were sufficiently (i.e., achieving MVPA guidelines of ≥ 150 min/week) vs. insufficiently active.Results: Prior to COVID-19, 68.2% of participants were classified as being sufficiently active, vs. 60.6% during COVID-19. The majority of participants reported experiencing some level of depressive symptoms (62.0%) or anxiety symptoms (53.7%). After controlling for covariates, changes in MVPA accounted for significant variability in the PHQ-9 (7.7%), GAD-7 (2.5%), and SWLS (1.5 %). Participants with clinically significant mental health symptomatology reported greater declines in MVPA than those who reported no symptoms. Conversely, participants who were sufficiently active during COVID-19 reported significantly lower depression and anxiety, and higher life satisfaction.Conclusion: Participants who experienced the greatest declines in MVPA reported relatively greater psychological distress and lower life satisfaction. While preliminary, these findings suggest the importance of maintaining and promoting physical activity during a period of pandemic.